2012
DOI: 10.5935/1678-9741.20120070
|View full text |Cite
|
Sign up to set email alerts
|

Time of arrival of patients with acute myocardial infarction to the emergency department

Abstract: Objectives: To characterize the profile of patients with acute myocardial infarction (AMI) treated at the emergency department and to verify the time of arrival of each patient (∆T). Identify how the patient was transported and to correlate Delta-T (∆T) with the treatment and the prognosis of each patient.Methods: Cross-sectional survey involving 52 patients with AMI admitted to the Emergency Department of a Teaching Hospital took part in the study from July to December 2010. Data collection was performed usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 14 publications
1
15
0
5
Order By: Relevance
“…Concerning the signs and symptoms of AMI, 90.6% of the participants who knew the term "infarction" also had adequate knowledge about AMI manifestations. A study with 52 participants who had AMI conducted in São Paulo showed that 100% of the respondents recognized that they had some of the classic symptoms of AMI, which are chest pain radiating to the arm, sweating and pain in the epigastric region (19) .…”
Section: Discussionmentioning
confidence: 99%
“…Concerning the signs and symptoms of AMI, 90.6% of the participants who knew the term "infarction" also had adequate knowledge about AMI manifestations. A study with 52 participants who had AMI conducted in São Paulo showed that 100% of the respondents recognized that they had some of the classic symptoms of AMI, which are chest pain radiating to the arm, sweating and pain in the epigastric region (19) .…”
Section: Discussionmentioning
confidence: 99%
“…The study to compare the prognosis and waiting time for specialized intervention reveals that the recognition of signs and symptoms of acute myocardial infarction by the patient was a determining factor for the demand for specialized care. 12 In qualitative research with women who suffered acute myocardial infarction, they showed little clarity in accurately assessing their cardiovascular risk, poor preventive health behaviors, and delayed in seeking care based on the symptoms. 13 Threefactors were elaborated by patientsas a proper behavior toreducethedelayin searching for health care after the onset of symptoms: identifying the symptomsas having origin from theheart, having anaction planreadyin case of an emergency, and being withsomeone ormaking contact with otherpeople.…”
Section: Discussionmentioning
confidence: 99%
“…(10) The predominant marital status was married/with a partner, in agreement with other studies. (9,11) Participants had similar socioeconomic characteristics, expressed by the dependence on the Unified Health System, low level of schooling and low family income. Also, one third was professionally inactive, due to unemployment or retirement.…”
Section: Discussionmentioning
confidence: 99%